THE COMMUNICATION COMPETENCE OF VISUAL READER AT VISUALLY IMPAIRED'S CINEMA - Karolina, Cut Meutia; Maryani, Eni; Sjuchro, Dian Wardiana (SCAD Independent, 2020)
Bioskop Harewos is a cinema that specialized in visually impaired film viewers in Bandung, Indonesia.  The cinema runs with a traditional and distinct watching process. Some important concepts used in this research are related to communication competences; Visually impaired; and film. Using a qualitative method with constructivism paradigm and case study approach, this research tries to uncover several aspects, such as the communication capabilities of Visual Readers in Bioskop Harewos; the management effort of Bioskop Harewos in enhancing the communication effectiveness between Visual Readers and visually impaired viewers; also the competency of communication skills that required by Visual Readers. The result of this study revealed that the communication skills of Visual Readers in terms of being a prompter to visually impaired viewers were still under expectation. In terms of improving communication skills, the manager of the Bioskop Harewos has made several introductions and pre-viewing activities, yet the result is not as expected. This research also found three key competencies that are a necessity to be possessed by Visual Readers.